Testing of Anti-atherogenic Drugs and Food Components on Cell Cultures: Assessment of Reliability - Jargin, Sergei V. (Puerto Rico Health Sciences Journal, 2010)
In the large series of publications started in 1986 (The Lancet, 2:595), and continuing until today, was reported that culturing of smooth muscle cells with the serum from coronary heart disease patients caused lipid accumulation in the cultured cells, while serum from healthy individuals had no such effect. The method was used for testing anti-atherogenic drugs. Numerous substances have been reported efficient in vitro against serum atherogenicity: statins, trapidil, prostaglandin E2, dibutyryl cyclic AMP, calcium antagonists, lipoxygenase inhibitors, carbacyclin, extracts of different mushrooms species, quid liver, krill meat, derivatives of garlic, black elder berries, calendula, violet flowers, hop cones, grape seeds etc. On the contrary, beta-blockers, phenothiazines, oral hypoglycemics etc. were reported to be pro-atherogenic. According to the common knowledge, anti-atherogenic agents can influence cholesterol synthesis, lipid metabolism in the liver, intestinal absorption or endothelial-mediated mechanisms. All these targets are absent in a cell culture. Inflammatory mechanisms, influenced by some anti-atherogenic agents, are also not reproduced in a cell monoculture. Therefore, conclusions and recommendations for practice formulated on the basis of cell culture experiments studying serum atherogenicity are questionable and require further substantiation.